PERAN SELF CONTROL DALAM MEMEDIASI PERILAKU BELANJA PRODUK FASHION DI E-COMMERCE - Isnaini, Nur Hidayah; Mahdaly, Alwiyah; Sayyida, Sayyida (Journal MISSY (Management and Business Strategy), 2025)
Business development through e-commerce is one of the strategies to increase sales volume, especially in a situation like today that uses technology, this research was conducted with the aim of finding out and proving whether there is a correlation between the influence of online customer reviews and live streaming on purchase decisions with self-control as a mediating variabel for consumers of e-commerce fashion products Shopee in Sumenep Regency. The research method carried out in this study uses a quantitative method, with a non-probability sampling technique of purposive sampling through the distribution of questionnaires, the use of samples in this study is 156 respondents.The results of the analysis in this study using SmartPLS 3 show that online customer reviews have a positive and significant effect on purchase decisions. Live streaming has a positive and significant effect on purchasing decisions. Self-control has a positive and significant effect on purchasing decisions. Online customer reviews mediated by self-control have a positive and significant effect on purchase decisions. Live streaming mediated by self-control has a positive and significant effect on purchasing decisions.